This is the way we see it : A Tribute to E.L.T. Mesens. - Weiss, Erich ([S.l.] : [s.n.])
King, Scott ; Nollen, Arno ; Eder, Martin ; Nova, Nils ; Davi, Barbara ; Wekua, Andro ; Weiss, Erich ; Galler, Thomas ; Turk, Gavin ; Deller, Jeremy ; Parker, Graham ; Magne F ; Zanni, Margot ; Lowe, Colin ; Delvoye, Wim ; Saville, Peter ; Blessmann, Anna
boek